ECTHR_COMMITTEE 24615/16 vom 26. September 2024 , AFFAIRE RAPUCCI c. ITALIE - Ecthr Committee (2024)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure civile;Article 6-1 - Délai raisonnable); Violation: 6;6-1